Significance of Frequencies, Compositions, and/or Antileukemic Activity of (DC-stimulated) Invariant NKT, NK and CIK Cells on the Outcome of Patients With AML, ALL and CLL. Issue 6 (July 2017) - Boeck, Corinna L.; Amberger, Daniel C.; Doraneh-Gard, Fatemeh; Sutanto, Wishnu; Guenther, Thomas; Schmohl, Joerg; Schuster, Friedhelm; Salih, Helmut; Babor, Florian; Borkhardt, Arndt; Schmetzer, Helga
Abstract : Invariant natural killer T (iNKT)/natural killer (NK)/cytokine-induced killer (CIK) cells are important for immune surveillance. (I) Novel combinations of antibody 6B11 (targeting the Vα24-Jα18-invariant T-cell receptor) with CD4/CD8/CD1d/Vα24 for iNKT subset detection and "T/NK cell-like"-iNKT subsets were defined. Compared with healthy peripheral blood mononuclear cells (MNC) (significantly) lower proportions of iNKT cells (6B11 + /6B11 + CD3 + /6B11 + CD161 + ), NK cells (CD3 − CD56 + /CD3 − CD161 + ), and CIK cells (CD3 + CD56 + /CD3 + CD161 + ) were found in peripheral blood MNC from acute myeloid (AML)/acute myeloid, lymphoid (ALL)/chronic lymphoid leukemia (CLL) patients in acute disease stages. Subtyping of iNKT cells revealed (significantly) higher proportions of CD3 + T cells and CD161 + NK cells in AML/ALL/CLL expressing 6B11 compared with healthy MNC. Prognostic evaluations showed higher proportions of iNKT/NK/CIK cells in favorable AML subgroups (younger age, primary, no extramedullary disease, achievement/maintenance of complete remission) or adult ALL and CLL patients. (II) iNKT/NK/CIK cell frequencies increased after (vs. before) mixed lymphocyte cultures of T-cell–enriched immune reactive cells stimulated with MNC/whole blood with or without pretreatment with "cocktails" (dendritic cells generating methods/kits inducing blasts' conversion to leukemia-derived dendritic cells from AML patients). Individual "cocktails" leading to "highest" iNKT cell frequencies could be defined. Antileukemic blast lytic activity correlated significantly with frequencies of iNKT/NK/CIK cells. In summary healthy MNC show significantly more iNKT/NK/CIK cells compared with AML/ALL/CLL MNC, a shift in the iNKT cell composition is seen in healthy versus leukemic samples and iNKT/NK/CIK cell-proportions in AML/ALL/CLL MNC samples correlate with prognosis. "Cocktail"-treated AML blasts lead to higher iNKT/NK/CIK cell frequencies and samples with antileukemic activity show significantly higher frequencies of iNKT/NK/CIK cells. Proportions of iNKT/NK/CIK cells should regularly be evaluated in AML/ALL/CLL diagnosis panels for quantitative/prognostic estimation of individual patients' antileukemic potential and their role in dendritic cells/leukemia-derived dendritic cells triggered immune surveillance.